Pelatihan Pemberdayaan Perpustakaan dan Mading Assalam Magazine di Pondok Pesantren Miftahul Mubtadiin Putri-Putri Ar Ridlo Krempyang Tanjunganom Nganjuk - asichul in'am; Vilasofia Yustikasari; Moch. Yaziidul Khoiiri; M. Shohibul Aziz (LP3M STAI Darussalam Krempyang Nganjuk, 2022)
Libraries and wall magazines are some of the tools used by students to deepen their knowledge and hone their creativity. At the Miftahul Mubtadiin Ar-Ridlo Islamic Boarding School there is a library called Assalam Magazine. However, this library is still not perfect because in terms of facilities and infrastructure it is still inadequate. The state of the library and wall magazine has quite a lot of devotees, but there is a drawback, namely the limited space for reading and visiting. The purpose of this assistance is to empower the library through the management process and increase the reading interest of the students. The approach used is Asset Based Community Development (ABCD), which is an approach by utilizing existing assets. As a result, the administrators of the library and wall magazines were able to increase their knowledge about the empowerment of libraries and wall magazines and how to overcome existing problems. After this program, they also began to add elements to the wall magazine, such as a wall magazine corner, the mading logo and have conducted a comparative study on the wall magazine, and the addition of a collection of books that will be carried out after the Maulud holiday.